2016
DOI: 10.1177/0042098015601579
|View full text |Cite
|
Sign up to set email alerts
|

Growing resources for growing cities: Density and the cost of municipal public services in Latin America

Abstract: We find that per capita municipal spending on public services is strongly and non-linearly correlated to urban population density. Optimal expenditure levels for municipal services are achieved with densities close to 9000 residents per square kilometre. In our study of about 8600 municipalities of Brazil, Chile, Ecuador and Mexico, 85% of all municipalities are below this ideal density level. This result provides strong policy support for densification, particularly in medium-sized cities of developing countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 45 publications
0
14
0
2
Order By: Relevance
“…The optimum value would be different when considering other factors. For example, Libertun de Duren and Guerrero Compeán (2016) found that optimal expenditure levels for municipal services were achieved with densities close to 9000 residents per square kilometre. Therefore, the density effect needs to be studied more comprehensively in the future, Second, the optimum density of the urban population may be determined by a city’s transport infrastructure and mode (Burton et al, 1996; Shirgaokar, 2015); for example, sprawl is the inexorable product of car-based living in the US (Glaeser and Kahn, 2004) and in Australia, but the opposite is true in Japan, with a high population density and an advanced public transport system (Garcia and Riera, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The optimum value would be different when considering other factors. For example, Libertun de Duren and Guerrero Compeán (2016) found that optimal expenditure levels for municipal services were achieved with densities close to 9000 residents per square kilometre. Therefore, the density effect needs to be studied more comprehensively in the future, Second, the optimum density of the urban population may be determined by a city’s transport infrastructure and mode (Burton et al, 1996; Shirgaokar, 2015); for example, sprawl is the inexorable product of car-based living in the US (Glaeser and Kahn, 2004) and in Australia, but the opposite is true in Japan, with a high population density and an advanced public transport system (Garcia and Riera, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In the form of f(density) , previous studies focused on the positive elasticity coefficient (see Table 1), considering density as equivalent to the population size of the unit area, and then, according to the logic of the optimum city size (Henderson, 1974; Mills, 1967; Mills and Ferranti, 1971), the optimum urban population density exists and can be reached at the balancing point of the economic effect and crowding effect. On the economic effect side, density affects productivity in several ways originating from the input-output relationship, externalities and beneficial specialisation (Ciccone and Hall, 1996; Fang et al, 2013; Libertun de Duren and Guerrero Compeán, 2016). For the same urban land area, a higher population density means higher population size, and the density economic effect contains three classical sources of agglomeration economies (Krugman, 1991; Marshall, 1890).…”
Section: Model and Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Libertun de Duren and Guerrero Compeán (2016) studied a panel of 8600 municipalities of Brazil, Chile, Ecuador and Mexico, for the years 2000 and 2010, and found that the relationship between urban population density and per capita municipal spending on public services was strong and U-shaped. Optimal expenditure levels for municipal services are achieved with densities close to 9000 residents per square kilometre.…”
Section: Literature Reviewmentioning
confidence: 99%
“…But even more important is that uncoordinated land use regulation across a metropolis can lead to urban sprawl or excessive densities with the attendant increase in per capita costs in providing basic services and infrastructure (Libertun and Guerrero Compean, 2016). In addition, coordinated land use regulation across the municipalities of a metropolis present investors with a predictable investment framework conducive to spatially rational outcomes guarding the efficiency of the spatial form that emerges or the negative externalities associated with mis-specified regulation.…”
Section: Introductionmentioning
confidence: 99%